The blood compatibility challenge. Part 2: Protein adsorption phenomena governing blood reactivity - Brash, John L.; Horbett, Thomas A.; Latour, Robert A.; Tengvall, Pentti (Acta biomaterialia, 2019)
[Display omitted] The adsorption of proteins is the initiating event in the processes occurring when blood contacts a “foreign” surface in a medical device, leading inevitably to thrombus formation. Knowledge of protein adsorption in this context has accumulated over many years but remains fragmentary and incomplete. Moreover, the significance and relevance of the information for blood compatibility are not entirely agreed upon in the biomaterials research community. In this review, protein adsorption from blood is discussed under the headings “agreed upon” and “not agreed upon or not known” with respect to: protein layer composition, effects on coagulation and complement activation, effects on platelet adhesion and activation, protein conformational change and denaturation, prevention of nonspecific protein adsorption, and controlling/tailoring the protein layer composition. This paper is part 2 of a series of 4 reviews discussing the problem of biomaterial associated thrombogenicity. The objective was to highlight features of broad agreement and provide commentary on those aspects of the problem that were subject to dispute. We hope that future investigators will update these reviews as new scholarship resolves the uncertainties of today.